2019
DOI: 10.1021/acs.joc.9b02315
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azulitriphyrins(1.2.1) and Related Benzocarbatriphyrins

Abstract: Bis(pyrrolylmethyl)azulene dialdehydes underwent intramolecularMcMurry coupling, and following oxidation with DDQ and addition of trifluoroacetic acid, gave aromatic azulitriphyrin cations. The proton NMR spectra for these contracted carbaporphyrinoids showed the internal CH upfield at ca. 2 ppm, while the bridging methine units appeared downfield between 8 and 10 ppm, demonstrating that the macrocycles possess significant 14π electron diamagnetic ring currents. Although protonated azulitriphyrins(1.2.1) prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Triphyrin analogues comprise a variety of macrocycles in which one or more pyrrole units of the triphyrin structure have been replaced by carbocycles, like in carbatriphyrins(3.1.1), 690 carbatriphyrins(2.1.1) ( 726 Fig. 126), 691 azulitriphyrins(1.2.1) ( 727 ), 692,693 or other types of carbatriphyrins, 694 including the triphyrin(2.1.1)-tetraphyrin(1.1.1.1) hybrid 737 . 695 Substitution of one pyrrole ring by other heterocycles also produces triphyrin analogues.…”
Section: Subporphyrinsmentioning
confidence: 99%
“…Triphyrin analogues comprise a variety of macrocycles in which one or more pyrrole units of the triphyrin structure have been replaced by carbocycles, like in carbatriphyrins(3.1.1), 690 carbatriphyrins(2.1.1) ( 726 Fig. 126), 691 azulitriphyrins(1.2.1) ( 727 ), 692,693 or other types of carbatriphyrins, 694 including the triphyrin(2.1.1)-tetraphyrin(1.1.1.1) hybrid 737 . 695 Substitution of one pyrrole ring by other heterocycles also produces triphyrin analogues.…”
Section: Subporphyrinsmentioning
confidence: 99%
“…In addition, [14]azulitriphyrin(2.1.1) 22a can be transformed into benzocarbatriphyrin(2.1.1) 23a, which shows porphyrin-like aromatic properties. 39 Ortho-phenylene and thiophene-fused oxatriphyrins(2.1.1) 25 were reported by Latos-Grażyński and co-…”
Section: Account Synlettmentioning
confidence: 94%
“…In addition, [14]azulitriphyrin(2.1.1) 22a can be transformed into benzocarbatriphyrin(2.1.1) 23a, which shows porphyrin-like aromatic properties. 39 Ortho-phenylene and thiophene-fused oxatriphyrins(2.1.1) 25 were reported by Latos-Grażyński and co- 37 The Ravikanth group prepared the nonsymmetric benzene-fused oxatriphyrin(2.1.1) 28a and thiatriphyrin(2.1.1) 28b in four steps starting from 1-benzofuran and 1-benzothiophene, respectively (Scheme 11). 42 The nonaromatic dibenzofuran/dibenzothiophene-based triphyrins(2.2.1) 30a and 30b, and their Re(I) complex were also reported by the same group (Scheme 10).…”
Section: Account Synlettmentioning
confidence: 99%
See 1 more Smart Citation
“…Okujima et al [ 97 ] and Lash et al [ 98 ] subsequently reported azulitriphyrin with triphyrin(2.1.1) framework. Intramolecular McMurry coupling of diformyltripyrrane is a key step for the construction of the triphyrin(2.1.1) framework ( Scheme 62 ) [ 99 ].…”
Section: Synthesis Of Azulene Derivatives Incorporated With Porphymentioning
confidence: 99%